A televisão e as vítimas: a rede de silêncio que acobertou crimes sexuais - Previdi, Ivandra (2016)
This is a research about the criminal investigation that resulted in the condemnation of the ex-physician Roger Abdelmassih to 278 years in prison, for sexual crimes perpetrated in the assisted reproduction clinic would command in São Paulo. Abdelmassih, now 73, assaulted the first patient when still a young doctor. Thereby, the main issue: how was it possible that this man acted for decades with impunity? From this question, derives the object of research: the silence that covered up the crimes, along with the silence of the victims themselves to begin with. To comprehend this fact, I have listed the following hypotheses: the fear that a possible complaint could turn back against the victims, the concern of losing the high amount of money invested in the ideal of motherhood and the feeling of inferiority towards the scientific knowledge – what has been proven by the depositions contained in the criminal process, which constitutes the corpus of this study. But even more emerged from the case files: beyond the victims themselves, there was a wide network of citizens who were aware of Abdelmassih´s criminal behaviour. Among them, there were some of his relatives and employees, physicians from other clinics, the medicine council, prosecutors, lawyers, and the mass media – including Globo TV, that did not air that which would be the first news report about the subject, based on the interviews of six women and edited almost one year before the scandal erupted. The extracts of the process are here analysed in the light of Communications and Journalism, with Eugenio Bucci, of Sociology and Philosophy, with Edgar Morin and Michel Foucault, and with the complementary support of Psychology and Law. Bucci teaches us how to see journalism as a democracy instrument, under an ethics perspective and the right to information. Edgar Morin sheds light on stretching Philosophy and Sociology to beyond the facts, which leads to a cultural-oriented approach to the events. And Michael Foucault brings the reflection on power, not as a someone else’s practice, but as a continuous torrent seeping into our daily life